Reducing production variability using factorial optimisation: A case study from the food-packaging industry. Issue 1 (1st January 2018) - Macak, Tomas; Hron, Jan; Ticha, Ivana
Abstract: In industry, many phenomena and events that arise that cannot be predicted because they represent changes in production. Such random effects and events can significantly influence all aspects of the manufacturing process. The optimal design of any production system can be generated based on a complete, correct set of input information. However, such a requirement is unrealistic, as manufacturing systems are affected by several random factors. Current practice is based on determining the worst possible conditions in which a production system could run (the longest possible duration of outages in the supply chain, extreme weather conditions in agriculture, etc.). This article aimed to identify factors influencing the variability of the manufacturing process in the field of CNC (Computer Numerical Control) machining for food production. A secondary aim was to minimise the variability of the manufacturing process using a factorial design. The variability reduction was verified using statistical F -tests. The study on reducing variability in production was performed at the Czech Yuncheng Plate Making Co., Ltd., a professional rotogravure cylinder–making company. The cylinders are used for the food industry.